Torta de algodón en dietas para cerdas de cría durante tres ciclos reproductivos continuos - Obando Correa, Hector; Moncada Bueno, Alberto (Instituto Colombiano Agropecuario, 2019)
At the Tibaitatá Experimental center of the Instituto Colombiano Agropecuario, ICA, located in Mosquera, Cundinamarca, at 2.640 meters above sea level, with an average temperature of 13°C and average annual rainfall of 641 mm, an experiment with sows was conducted during three consecutive cycles of gestation and lactation, feeding high levels of cotton seed meal without the addition of gossipol antidotes. The investigation involved 40 sows, Duroc x Landrace and Landrace x Ducor crosses, of different ages with initial wetht fluctuating between 120 and 240 kilograms. The animals were distributed at random in four treatments: 1- Control: Corn + Soybean meal (A); 2. Cotton seed meal: 9,4% (B); 3- Cotton seed meal: 15% ; C) and 4 Cotton meal: 15% + lisine and metionine D). Three Duroc boars were used, serving an equal number of sows in each treatnient. During gestation the females were kept in corrals of kikuyu grass pasture (Pennisetum clandestinum) and fed cotton seed meal in rations of 1 kg. daily. They were weighted every 36 days beginning the day of breeding. During the lactation period, the sows were given free-choice food and water, with the predetermined treatments for the rations. The sow and piglets were 107 weight at parturition and 21, 35 and 42 days following parturition. The established practice of removing teeth and ear- marking the piglets was performed 24 hours after birth; 150 mg of iron was injected on day three, and 8 days after birth they began their only diet, a 20% protein ration made of corn and soybean meal and at 14 days all males were castrated. During gestation, the females were offered a diet of 14% protein and during lactation, 16% protein. In both stages the levels of cotton seed meal (content of free gossipol: 0,036%) for the four treatments were 0, 9, 4, 15 and 15% + lisine andmetionine. The results obtained during the three consecutive gestations were the following: Increase in weight of the sow: A) 31,5 kg; B) 36,5 kg; C) 35,3 kg and D) 32,7 kg. Number of piglets born A: 9,4; B: 8,3; C: 10,7 and D: 7,7. Weight of the piglets: A) 1,3 kg; B) 1,4 kg; C) 1,4 kg and D) 1,5 kg. In the previous parameters, no significant differences were detected among the treatments, suggesting that during this period 100% soybean meal can be replaced for cotton seed meal in the diet for extended lengths of time without reducing reprodutive performance of the sow. In the three lactations, the average results were as follows: 1) Weight changes in the sow: A: 1,4 kg; B) 11,2 kg; C) 6,6 kg; D) 9,4 kg. 2- Number of weaned piglets: A) 7,4 kg; B) 7,1; C) 7,3 and D) 7,8; 3Weight of weaned piglets: A) 8,9 kg; B) 8,3 kg; C) 8,4 kg; D) 8,6 kg. 4- Percent mortality of piglets: A) 21,21/o; B) 27,2%; C) 27,3% and D) 14,0%. In the previous parameters, no significant difference was found among treatments excep a higher weight gaon in sows fed diets containing cotton seed meal. Finding a low mortality rate in piglets under treatment D, a clear advantage could not be established. These results suggest that it is possible to replace 84,3% of the soy-bean meal with cotton seed meal without endangering the yield of lactating sows and their litters. B: The feed consumption per sow was, A: 247,4 kg; piglet's consumption during lactation was A: 12,5 kg; B: 14,7 kg; C: 13,4 kg and D: 15,0 kg these data corraborates even more the possibility of feeding high levels of cotton seed meal during lactation in this experiment was: A) 80%; B) 9011o; C) 80% and D) 80% a number that reveals the benevolence of cotton seed meal.